Identifikasi Bakteri Escherichia Coli dari Air Minum Unggas di Peternakan Layer - Binti Khopsoh; Riska Faradila; Anna Lidiyawati; Nining Haryuni; Lestariningsih Lestariningsih; Tika Afrilia (Faculty of Agriculture, Musamus University, 2021)
This study aims to identify Escherichia coli bacteria from drinking water poultry in layer farms, Ponggok sub-district, Blitar district. 7 samples of water were collected from layer farms in the village of Kebonduren Ponggok Blitar. Water samples were examined for Escherichia coli bacteria using the Most Probable Number (MPN) method and analyzed descriptively. The results in this study were from 7 farms found 1 farm whose drinking water was contaminated with Escherichia coli bacteria, the number of E.coli was 210 MPN/100 ml, these results still met the MPN Coliform threshold value for class II farm water according to PP no 82 in 2001, which was 5000 MPN/100 ml of water and 2000 MPN/100 ml of E. coli.